Money and monetary policy in times of crisis - Hanna Armelius; Carl Andreas Claussen; David Vestin (Economic Commentaries, 2020)
Central banks around the world have implemented extensive measures to alleviate the effects of the corona pandemic on the economy. Many of the measures involve creating large volumes of new money. But how is money created and who ends up holding it? In this commentary, we explain how money is created and destroyed in the current financial system, what roles the banks and the Riksbank have and how different course of action by the banks and the Riksbank influence the amount of money. At the end of the commentary, we use examples from the Riksbank's crisis measures to illustrate how monetary policy influences the economy and the amount of money.
Keywords: E51; E52; E58; G2; H12; 330; Monetary policy; Money creation; Crisis